Treatment of cartap wastewater through electro-fenton process - Gumaling, Riza P.
Cartap is not regulated in the Philippines despite its toxic effects to both human and organisms. As of present, it is slowly getting attention and was recently labeled as an emerging contaminant. Previous studies conducted for cartap-contaminated wastewater involve Fenton, fluidized-bed Fenton and photocatalytic oxidation. In this study cartap wastewater was treated by employing electro-Fenton (EF) process with initial pH, Fe²? and H2O2 concentrations as parameters. Parametric studies were first done by varying each parameter then selecting the highest cartap removal as the best conditions. After which, comparison of Fenton experiments was conducted and the kinetics of cartap degradation was investigated. Finally, PO4¯³, NO3¯ and Cl¯ at 0 mM to 10 mM was investigated. Parametric results indicated highest cartap removal at 1.6 pH, 3.0 mM and 60 mM H2O2 at constant conditions 5 mM cartap and 1.0A current supplied. Comparisons of Fenton and EF results have shown superior cartap removal. The kinetics of cartap degradation followed pseudo-second order with initial rate constant of 1.10E-05 mM¯¹s¯¹and an average constant of 2.08E-02 mM¯¹s¯¹. Further optimization studies were conducted using CCD and results have shown 1.84 pH, 1.28 mM, and 26.03 mM H2O2 as optimized conditions at constant cartap concentration, 1.5A and room temperature. Inhibition effects of inorganics have proven PO4¯³ to have the highest effect in inhibiting c